First Summer Course in Animal Law in Scandinavia hosted by Aarhus University - Sacha Lucassen (Universitat Autonoma de Barcelona. Facultat de Dret, 2018)
Last July the first summer course in Animal Law took place at Aarhus University, Scandinavia, one of Europe’s most renowned universities. The course was created and lectured by Sacha Lucassen (MA Animal Law and Society, UAB - 5th Edition) and welcomed students not only from all over Europe, but even from Vietnam, Kenya, China and Australia. It revolved around the main question “How and to what extend are – or should - animals be protected by the law?” Experts in different domains within the scope of Animal Law delivered valuable contributions to the course during several guest lecturers. The course put Animal Law on the academic program in Denmark and will take place again next summer.